1990
DOI: 10.1159/000281732
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Acidification of Urine in Patients Treated for Infected Renal Stones

Abstract: The effects of ammonium chloride, methenamine hippurate and ascorbic acid on urinary pH was studied in 14 normal subjects. A statistically significant reduction of urinary pH was recorded with ammonium chloride in daily doses of 1.5 and 3 g, but not with 2g of methenamine hippurate or 1.8 g of ascorbic acid. Long-term treatment with ammonium chloride in doses between 1.5 and 3 g was given to 11 patients in order to reduce the risk of new stone formation or growth of fragments remaining after disintegration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…Maintaining urinary pH below 6 or even below 5.5 is thought to be necessary to achieve bactericidal concentrations of formaldehyde [240]. Studies of ascorbic acid in dosages of up to 4 g per day have shown no significant effect on mean urinary pH [243][244][245], and dosages as high as 12 g per day or more frequent administration (eg, every 4 h) may be required to adequately acidify the urine [238]. Ammonium chloride might be more effective in acidifying the urine, but the potential for metabolic acidosis is a concern [244].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Maintaining urinary pH below 6 or even below 5.5 is thought to be necessary to achieve bactericidal concentrations of formaldehyde [240]. Studies of ascorbic acid in dosages of up to 4 g per day have shown no significant effect on mean urinary pH [243][244][245], and dosages as high as 12 g per day or more frequent administration (eg, every 4 h) may be required to adequately acidify the urine [238]. Ammonium chloride might be more effective in acidifying the urine, but the potential for metabolic acidosis is a concern [244].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Struvite precipitates only at pH >7.2 [83][84][85]. Proteus mirabilis accounts for more than half of all urease-positive infections [86,87] E U R O P E A N U R O L O G Y X X X ( 2 0 1 4 ) X X X -X X X measures include complete surgical stone removal [11], short-or long-term antibiotic treatment [88], urinary acidification using methionine [49] or ammonium chloride [50], and urease inhibition [51,52]. For severe infections, acetohydroxamic acid (Lithostat) may be an option (Table 12).…”
Section: Struvite and Infection Stonesmentioning
confidence: 99%
“…Unfortunately, however, the length of the treatment period has never been clearly established. Several preparations for lowering urine pH might also be useful in treating patients with infected renal stones [19,20]. …”
Section: Discussionmentioning
confidence: 99%